Seno dérmico. Presentación de 4 casos. - Sardiñas Hernández, Norberto; Maya Entenza, Carlos; Pascual Gispert, Joaquín; Rojas Massipe, Edelsia; García Machado, Lupo (Revista Cubana de Pediatría, 2024)
Se presentan 4 casos de pacientes con seno dérmico.